2020
DOI: 10.1007/s12144-020-00998-5
|View full text |Cite|
|
Sign up to set email alerts
|

First look at the five-factor model personality facet associations with sensory processing sensitivity

Abstract: The current paper presents an examination of the associations between Five-Factor Model (FFM) personality facets and Sensory Processing Sensitivity (SPS) to understand which personality facets are especially relevant for SPS. Associations between SPS and the FFM personality domains and facets were examined in older adolescents and young adults (Study 1) as well as older children and young adolescents (Study 2). The most relevant facets were within the Neuroticism and Openness domains, although not all facets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
(42 reference statements)
3
15
1
Order By: Relevance
“…Our sample’s score on the Big 5 questionnaire and their responses on the interviews were in line with quantitative personality research that showed that SPS correlates with negative emotionality and openness to experience [ 5 ]. However, our identified themes suggest that it is too simplistic to state that SPS is just a combination of negative emotionality and openness to experience; instead, SPS seems to encompass a specific profile, supporting previous quantitative work on personality profiles of SPS [ 6 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our sample’s score on the Big 5 questionnaire and their responses on the interviews were in line with quantitative personality research that showed that SPS correlates with negative emotionality and openness to experience [ 5 ]. However, our identified themes suggest that it is too simplistic to state that SPS is just a combination of negative emotionality and openness to experience; instead, SPS seems to encompass a specific profile, supporting previous quantitative work on personality profiles of SPS [ 6 ].…”
Section: Discussionsupporting
confidence: 78%
“…SPS is heritable (around 45%), and common, with around 20%–30% of the population considered high in SPS (also “highly sensitive”) [ 2 , 3 , 4 ]. Although SPS correlates with other personality traits, especially negative emotionality and openness to experience, SPS is largely distinct from Big 5 personality dimensions or other temperament traits and may be considered a profile of lower-level personality facets [ 3 , 5 , 6 , 7 , 8 ]. In the past, sensitivity to environments was exclusively regarded as a risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…The authors conclude that the relationships between SPS and personality traits and affect are complex configurations, and SPS is relatively distinct from other personality traits and affect in both children and adults. Bröhl et al (2020) observed that for sensory processing sensitivity the most relevant variables were neuroticism and openness to experience. Extraversion was less related to sensory processing sensitivity, while the relationships between SPS and conscientiousness and agreeableness were of little importance.…”
Section: Introductionmentioning
confidence: 99%
“…Research findings suggest an association between SPS and personality traits and between SPS and positive and negative affect (e.g., Lionetti et al, 2019 ; Bröhl et al, 2020 ). When trying to define the relationship between SPS and the Big Five personality traits, Lionetti et al (2019) adopted the three-factor solution of SPS proposed by Smolewska et al (2006) : Ease of Excitation – EOE, Aesthetic Sensitivity – AES, and Low Sensory Threshold – LST.…”
Section: Introductionmentioning
confidence: 99%
“…The domain level meta-analysis by Lionetti et al ( 2019) and the facet level association analysis by Bröhl et al (2020) indicated that HSPs score above average on facets of Neuroticism (especially facets describing internalizing tendencies), as well as facets of Openness to Experience (especially facet Aesthetics). We additionally expect that participants to score below average on some facets of Extraversion (especially the facet Excitement-Seeking).…”
Section: Lay Theory Perspectivementioning
confidence: 99%